Studi simulasi teknik phising menggunakan zphiser untuk kesadaran keamanan siber - Ofelius Laia; Juwita Febry Cahyani Zendrato; Emanuel Gowasa; Rifadil Anugrah Harefa; Marlus Aval Adi Nazara; Nobel Fotumbu Zebua (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2026)
Phishing is one of the most common and dangerous cyber attacks as it can trick users into providing sensitive information such as usernames, passwords, and personal data. This study aims to simulate Phishing techniques using the Zphisher tool as an educational medium to improve cybersecurity awareness. The method used is a quasi-experimental approach involving 30 participants exposed to Phishing scenarios in a controlled environment using Kali Linux. The results show that 83% of participants clicked the Phishing link and 60% entered their credentials, while 40% demonstrated awareness by avoiding further interaction. These findings indicate that cybersecurity awareness is still relatively low, but Phishing simulation is effective as an experiential learning tool.